Bernardo García Díaz (Editor) La huelga del Río Blanco (1907-2007) - Artaza Barrios, Pablo (Cuadernos de Historia, 2008)
SEV Gobierno del Estado de Veracruz, México, 2007, 298 páginas. ISBN: 970-670-145-1